Pemberian Diet DM RG pada Pasien dengan Radiculopathy, Diabetes Mellitus, Essential Hypertension, Spondylosis, Spinal Stenosis - Ratu Shafa Aqilla (Lembaga Pengembangan Kinerja Dosen, 2025)
One of the key indicators of nation’s health development is life expectancy, which reflects the overall quality of public health. As life expectancy increases, the prevalence of non-communicable diseases (NCDs) also tends to rise, with Type 2 Diabetes Mellitus (DM) being one of the most common. In Indonesia, the number of individuals with Type 2 DM has reached approximately 10.7 million, and this figure is projected to increase significantly to 21.3 million cases by 2030, posing a serious public health challenge. This study aimed to describe the process of clinical nutrition care based on the Nutrition Care Process (NCP) for a patient diagnosed with Radiculopathy accompanied by Non-Insulin-Dependent Diabetes Mellitus (without complications), Essential (Primary) Hypertension, Spondylosis, and Spinal Stenosis, through the application of a regulated diabetic diet (DM RG) during hospitalization. The case study was conducted in November 2024 at RSI Ayani Surabaya and involved systematic monitoring of food intake and clinical outcomes during treatment. Findings indicated that within three days of observation, the patient’s dietary intake reached the target goals, demonstrating effective implementation of the prescribed meal plan. From physical and clinical monitoring, a notable decrease in blood pressure was observed on the second and third days, suggesting improvements in cardiovascular response to dietary management. Additionally, the patient’s temperature, pulse, respiratory rate, and oxygen saturation remained within the normal range throughout the treatment period, further supporting the effectiveness of the intervention. These results emphasize the importance of structured nutrition care in managing patients with multiple comorbidities, particularly those with diabetes and hypertension, as dietary regulation plays a central role in stabilizing health conditions. Overall, the study demonstrates that the application of the NCP framework combined with consistent monitoring can lead to positive patient outcomes and highlights its potential as a model for improving clinical nutrition management in hospital settings.